Benzofuroxan Derivatives as Potent Agents against Multidrug‐Resistant Mycobacterium tuberculosis. (9th February 2021) - Fernandes, Guilherme F. S.; Campos, Débora L.; Da Silva, Isabel C.; Prates, João L. B.; Pavan, Aline R.; Pavan, Fernando R.; Dos Santos, Jean L.
Abstract: Tuberculosis (TB) is currently the leading cause of death related to infectious diseases worldwide, as reported by the World Health Organization. Moreover, the increasing number of multidrug‐resistant tuberculosis (MDR‐TB) cases has alarmed health agencies, warranting extensive efforts to discover novel drugs that are effective and also safe. In this study, 23 new compounds were synthesized and evaluated in vitro against the drug‐resistant strains of M. tuberculosis . The compound 6‐((3‐fluoro‐4‐thiomorpholinophenyl)carbamoyl)benzo[ c ][1, 2, 5]oxadiazole 1‐ N ‐oxide (5 b ) was particularly remarkable in this regard as it demonstrated MIC90 values below 0.28 μM against all the MDR strains evaluated, thus suggesting that this compound might have a different mechanism of action. Benzofuroxans are an attractive new class of anti‐TB agents, exemplified by compound 5 b, with excellent potency against the replicating and drug‐resistant strains of M. tuberculosis . Abstract : Overcoming resistance : Benzofuroxan derivatives with anti‐ M. tuberculosis activity have been developed, some of which had potent activity against multidrug‐resistant TB strains and a high selective index against MRC‐5 cell lines. One compound had MIC90 values below 0.28 μM against five MDR‐TB strains and might have a mechanism of action different from that of the others.